New Developments in High-Temperature Measurement Techniques - Hartmann, Jürgen (International Journal of Electrical and Computer Engineering Systems, 2014)
Temperature can be measured via emitted thermal radiation of the measured object using Max Planck’s law of thermal radiation, which describes the emission of thermal radiation as a function of temperature of an ideal black body. However, thermal radiation measurement requires accurately calibrated detectors. The calibration of such detectors has been significantly improved in the last years, yielding calibration uncertainties of the spectral responsivity of detectors down to 10-4 in National Metrology Institutes. The paper briefly reviews the experimental and physical principles of optical temperature measurement via emitted thermal radiation and then covers recent developments in calibration technologies. Finally, practical methods for transferring these low uncertainties already achieved in the National Metrological Institutes to industry are outlined.